Realita Hambatan Pencatatan IAS 41 (Aset Biologis) Bagi UMKM Perikanan Dan Peternakan Di Jawa Timur - Mar'a Elthaf Ilahiyah; I Made Laut Mertha Jaya (Universitas Gorontalo, 2020)
Biological assets are a unique type of asset, because they undergo growth transformation, and are able to produce an output. This transformation consists of the process of growth, degeneration, production and procreation that can cause a variety of changes qualitatively and quantitatively the life of the asset. This study aims to determine the problem of the reality of obstacles in the application of recording IAS 41 for SMEs fisheries and farming in East Java. Data collection was carried out through the Group Group Discussion (FGD) grouping technique. This data is then processed through three stages, namely: 1) data reduction, 2) data presentation, 3) data analysis and drawing conclusions based on predetermined theories. The results showed that market prices that occurred in Indonesia could not be used as a basis for measuring the value of biological assets in some MSMEs fisheries and farming in East Java. This is because some MSME fisheries and farming actors in East Java are still doing their own estimates in accordance with the conditions of their biological assets. Thus, existing market prices give rise to unreliable information, which allows changes in estimates that differ from time to time according to the life of biological assets.